Periodisasi dan Perkembangan Peradaban Islam dan Ciri-Cirinya - Fadilatul Husna; Fatimah Lubis; Sukma Wardani; Sri Al Fatia (Journal on Education, 2023)
The purpose of this study is to determine the periodization and development of Islamic civilization, namely progress and intellectual and spiritual levels that make a civil society. Islamic civilization started from the periodization of the Prophet Muhammad saw. to the development of Islam to this day. The periodization of Islamic civilization is a feature of history which examines events in the context of time and place with various benchmarks. The Umayyads, the Abbasid period, the Mamluk period, the Ottoman period, the Contemporary Islamic World period. The method in this study used the method (library research) by collecting a number of literature relating to the problem and research objectives. Data collection with the results of previous research which supports data on periodization research and the development of Islamic civilization.